Aspirin is Involved in the Cell Cycle Arrest, Apoptosis, Cell Migration, and Invasion of Oral Squamous Cell Carcinoma - Zhang, Xiaoqi (Int J Mol Sci, 2018)
Oral squamous cell carcinoma (OSCC) is one of the most common cancers worldwide. In China, its 5-year survival rate is roughly 50%, owing to acquired chemotherapeutic resistance and metastasis of the disease. Accumulating evidence demonstrates that aspirin (ASA) acts as a preventive or therapeutic agent in multiple cancers; however, anti-tumor activities induced by aspirin are unclear in OSCC. To investigate the possible role of aspirin in OSCC development, we first employed bioinformatics to analyze the anti-OSCC effects of aspirin. We performed a genetic oncology (GO) enrichment analysis using the Database for Annotation, Visualization, and Integrated Discovery (DAVID), and the protein–protein interaction (PPI) network analysis by Cytoscape for differentially expressed genes (DEGs). We also evaluated the potential effects of aspirin on cell proliferation, invasion, migration, and apoptosis in two well-characterized OSCC cell lines (TCA8113 and CAL27). The bioinformatic results revealed that aspirin could inhibit proliferation by blocking the cell cycle, and could reduce migration and invasion via the PI3K-Akt and focal adhesion pathways. We found that ASA could downregulate the OSCC cell proliferation colony formation, invasion, and migration, as well as upregulate apoptosis. Furthermore, we found that ASA suppressed the activation of the focal adhesion kinase (FAK) and the phosphorylation of Akt, NF-κB, and STAT3. Overall, our data suggested that ASA may be developed as a chemopreventive agent to effectively treat OSCC.